Kaplan & Sadock's study guide and self-examination review in psychiatry - Sadock, Benjamin J, 1933-; Ruiz, Pedro, 1936-; Sadock, Virginia A. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"This study guide is an excellent aid in preparing for boards and other psychiatry exams and in reinforcing your knowledge. It offers chapter overviews of Synopsis, Tenth Edition and over 1,600 multiple-choice questions with discussions of correct and incorrect answers"--Provided by publisher
Includes index
Includes bibliographical references
13
Keywords: Mental Disorders -- Examination Questions; Psychiatry -- Examination Questions; Psychiatry -- Examinations, questions, etc; Psychiatry -- Examinations -- Study guides